2020
DOI: 10.1002/jcph.1703
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Subcutaneous Sarilumab and Intravenous Tocilizumab Following Single‐Dose Administration in Patients With Active Rheumatoid Arthritis on Stable Methotrexate

Abstract: We assessed pharmacokinetics (PK), pharmacodynamics (PD), and PK/PD relationships of interleukin-6 (IL-6), soluble IL-6 receptor, and C-reactive protein (CRP) in serum, and absolute neutrophil count (ANC) in blood following single doses of subcutaneous sarilumab versus intravenous tocilizumab (NCT02097524) from patients with rheumatoid arthritis (RA) who are inadequate responders to methotrexate (MTX) and on a stable dose of MTX. Patients with RA randomized (1:1:1:1) to single-dose sarilumab (150 or 200 mg sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…This dosing regime was associated with a significant improvement in symptoms in RA patients [ 18 ]. The concentration in the cell culture experiments was based on the maximum concentration (Cmax) in serum as measured in pharmacokinetic studies of sarilumab-treated patients [ 19 , 20 ]. However, in vitro inhibition of IL-6 signaling was already achieved by much lower concentrations of sarilumab.…”
Section: Methodsmentioning
confidence: 99%
“…This dosing regime was associated with a significant improvement in symptoms in RA patients [ 18 ]. The concentration in the cell culture experiments was based on the maximum concentration (Cmax) in serum as measured in pharmacokinetic studies of sarilumab-treated patients [ 19 , 20 ]. However, in vitro inhibition of IL-6 signaling was already achieved by much lower concentrations of sarilumab.…”
Section: Methodsmentioning
confidence: 99%
“…However, anti-IL-6 receptor therapies directly attenuate the levels of downstream molecules including CRP. In this specific setting, measuring IL-6 rather than CRP might be rationale, even though IL-6 levels usually rise after the first infusions of IL-6 receptor antagonists [83,84]. A recent paper showed that persistently high levels of IL-6 despite treatment with tocilizumab may predict future relapses [85].…”
Section: Inflammatory Molecules Cytokines and Cell Adhesion Moleculesmentioning
confidence: 99%
“…This could, in part, also be due to differences in their modes of action. Our results imply that 100 μg/ml tocilizumab (the concentration in plasma following the usual dose in humans ( 24 )) can block IL-6 concentrations of no more than 1 ng/ml. Importantly, anti-IL-6 and anti-IL-6R mAbs have been found to reduce systemic CRP levels to less than 4 and 1 mg/l ( 23 , 26 ), respectively, which does not indicate full inhibition of IL-6 bioactivity.…”
Section: Discussionmentioning
confidence: 68%
“…Given previous estimates indicating weak diffusion of plasma mAb into lymph nodes and interstitial lung tissue (8.46% and 14.9% of that in plasma, respectively) ( 21 , 22 ) and the established pharmacokinetics/pharmacodynamics of siltuximab ( 23 ) and tocilizumab ( 24 ), we assumed the mAb concentration in lymph nodes (iMCD scenario) or BAF (COVID-19 scenario) to be 10% of that in plasma. Because of uncertainty around mAb biodistribution, particularly into BAF (unknown but expected to be low: ~0.1–0.3% of that in plasma; see Supplementary Methods ), we also include results with mAb penetration into lymph nodes and BAF of 100% and 1% of the concentration in plasma as Supplementary Data .…”
Section: Methodsmentioning
confidence: 99%